Employment and wage status of the ultra poor - Halder, Shantana R. (Research and Evaluation Division, Brac, 2019)
This report looked into the employment status of the ultra poor and factors affecting the extent of employment. Findings showed that 92% of the households were with economically active population. Majority of the rest 8% were female-headed households mostly depending on others' help. Sixty-six percent of the economically active population participated in the labour force. The prevalence of child labour was 12.7% and 2.5% respectively among boys and girls aged 6-14 years. For the ultra poor lacking education and skills, one of the ways of increasing their household income was an addition of household members in the active labour force. This was true for the household having such potentiality. For households without physically acuve members it could not be the option. Secondly, although an addition in the amve labour force was one of the alternatives to increase income the rate of return from such addition was not same for males and females. The income labour ratio for male was higher than female. The existing gender division of labour, discriminative wage variations disfavouring females, limited female employment opportunities were the major reasons behind this. Thirdly, due to significant variations in the extent of employment in different region any development programme would not be equally beneficial for all regions.